2018
DOI: 10.1002/jls.21574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethical Leadership and Interactional Justice on Employee Work Attitudes

Abstract: The purposes of the current study were to (a) examine the direct effects of ethical leadership on three employee work attitudes—affective organizational commitment (AC‐ORG), affective commitment to the supervisor (AC‐SUP), and job satisfaction and (b) explore the mediating roles of two types of interactional justice—interpersonal justice (IPJ) and informational justice (IFJ)—on the effects of ethical leadership and employee work attitudes. Data were collected from 862 participants and structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 82 publications
1
24
1
Order By: Relevance
“…Since the ratings of followership and leadership behaviors were collected from the same source (i.e., middle managers), there was the possibility of common source bias (Charoensap, Virakul, Senasu, & Ayman, ). To reduce the likelihood of a common source variance, Harman's single factor test was conducted to see if a one‐factor solution would explain a significant proportion of the variance in the data (Podsakoff, MacKenzie, Lee, & Podsakoff, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the ratings of followership and leadership behaviors were collected from the same source (i.e., middle managers), there was the possibility of common source bias (Charoensap, Virakul, Senasu, & Ayman, ). To reduce the likelihood of a common source variance, Harman's single factor test was conducted to see if a one‐factor solution would explain a significant proportion of the variance in the data (Podsakoff, MacKenzie, Lee, & Podsakoff, ).…”
Section: Resultsmentioning
confidence: 99%
“…One potential limitation of the current study is common source bias, since ratings of TLB and EFB were self‐reported by respondents (Charoensap et al, ). However, the results of exploratory and confirmatory factor analysis showed a single‐factor solution was inadequate, thereby reducing the likelihood of a common source affecting the results (Podsakoff et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although ethical leadership is a recent topic of interest for many researchers, it lacks in-depth research to uncover the explanatory mechanism linking ethical leadership to outcomes of followers [1]. Most literatures have examined the relationship between ethical leadership and employee attitude, or counter-productive or extra-role behaviors, such as organizational citizenship behavior, knowledge sharing, whistleblowing, bullying, voice, deviance, creativity, moral cognition, misconduct, emotional exhaustion, and compassion [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In particular, the unknown link between ethical leadership and work performance has recently drawn attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation, the interest was in the interactional aspect of justice as an independent construct that has stipulated relationships with job satisfaction and organizational commitment (Charoensap et al, 2019;Wang et al, 2012), which may be uniquely important to journalists as intensive communication workers. Methodologically, limiting the number of constructs was also important to ward off potential multicollearity issues (Kalnins, 2018).…”
Section: Perceived Organizational Justice Scalementioning
confidence: 99%